Indirect genetic effects on the sociability of several group members. (January 2017) - Anderson, Blake B.; Scott, Andrew; Dukas, Reuven
Abstract : Indirect genetic effects (IGEs) are a major driver of social evolution, but much of the experimental work pertaining to IGEs on social behaviour has focused on the effect of stimulus individuals on single focal individuals. We extended IGE research to examine how stimulus individuals influence social interactions among several focal individuals. Specifically, we relied on recent work on social behaviour in fruit flies to examine whether IGEs cause 12 stimulus flies of distinct genotypes to alter social interactions within groups of six focal flies. The social behaviour of focals was significantly affected by the genotype of the stimulus flies. Focals were closer together when grouped with stimulus flies from genotypes that were close together than when grouped with stimulus flies from genotypes that were farther apart. A mechanism mediating this effect was the encounter rate between focal flies, which was lowest when the focal flies were grouped with stimulus flies of the more cohesive genotypes. Highlights: Indirect genetic effects (IGEs) are a major driver of social evolution. We examined how stimulus genotypes influence sociability of several focals. Focals' sociability was significantly affected by the stimulus genotypes. A mechanism mediating this effect was the encounter rate between focal flies. Focals' encounter rates were lower when grouped with more cohesive stimulus flies.